Internet journalism in cyberculture and its effect on adult attitude - Kayisli, Korhan (Sila Science, 2012)
Internet as a communication tool constantly constrains us to change our lifestyles, cultural habits, values and attitudes in a positive or negative way. This causes us to modify significantly the habits we have acquired in our traditional way of living. At this juncture we face two values: In the first place, cyberculture; and in the second place, internet journalism which is an important factor in the pattern of cyberculture. These two concepts are determining factors in the attitude of adults. The aim of this study is to examine the effect of internet journalism which is a factor in the construction of cyberculture and its influence on the attitude of adults.
Keywords: Internet journalism; Cyberculture; Internet; Adult; Attitude